Analysis of Batak Cultural Values in Supporting Economic Development in the Perspective of Maqashid Syariah - Alfioni Saragi; Rahmi Syahriza; Purnama Ramadani Silalahi (Universitas KH. Abdul Chalim Mojokerto, 2024)
Batak culture is threatened with extinction because it is no longer lived and internalized by the community, while several Batak values can support economic development in the city of Medan. This study aims to analyze Batak cultural values that support economic development in the perspective of maqashid sharia in the city of Medan. Qualitative research methods were used in this study with an ethnographic approach in which primary and secondary data were collected. Primary data were obtained through observation and interviews with educational figures, religious figures, and Batak traditional figures. Data analysis techniques include descriptive analysis, which consists of three steps: data reduction, data presentation, and conclusion drawing. The results of the study indicate that the Batak cultural values of Marsipature Hutanabe, Habonaron do Bona, and Sahata Saoloan Satumtum Sapartahian can support economic development in the city of Medan but have not been implemented well by the Medan community.